Konsep Kebijakan Moneter Prespektif Al - Marqizi - Misbah Romadona Tanjung; Allans Prima Aulia; Amaliya Zahara (Yayasan Lembaga Studi Manarul Ilmi, 2025)
Monetary policy is an important instrument in maintaining the economic stability of a country. In Islamic economic thought, Al-Maqrizi made significant contributions related to monetary policy, particularly in analyzing inflation and its impact on the economy. Al-Maqrizi distinguished inflation into two types, namely natural inflation due to external factors such as natural disasters and inflation caused by human error, such as poor monetary policy, corruption, and circulation of low-quality money. He also emphasized the importance of using gold and silver-based currencies to maintain economic stability, and highlighted the negative impact of printing excessive amounts of money without the support of intrinsic value. This study uses a qualitative method with a literature study approach to analyze Al-Maqrizi's thoughts and their relevance to modern monetary policy. The results show that Al-Maqrizi's thoughts are still relevant in the current economic context, especially in understanding the factors that affect inflation and the importance of a stable and equitable monetary policy. Thus, this study provides new insights in evaluating monetary policy based on Islamic economic principles that are more oriented towards the welfare of society. Kebijakan moneter merupakan instrumen penting dalam menjaga stabilitas ekonomi suatu negara. Dalam pemikiran ekonomi Islam, Al-Maqrizi memberikan kontribusi signifikan terkait kebijakan moneter, khususnya dalam menganalisis inflasi dan dampaknya terhadap perekonomian. Al-Maqrizi membedakan inflasi menjadi dua jenis, yaitu inflasi alamiah akibat faktor eksternal seperti bencana alam dan inflasi yang disebabkan oleh kesalahan manusia, seperti kebijakan moneter yang buruk, korupsi, serta peredaran uang berkualitas rendah. Ia juga menekankan pentingnya penggunaan mata uang berbasis emas dan perak untuk menjaga stabilitas ekonomi, serta menyoroti dampak negatif dari pencetakan uang dalam jumlah berlebihan tanpa dukungan nilai intrinsik. Studi ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan untuk menganalisis pemikiran Al-Maqrizi dan relevansinya terhadap kebijakan moneter modern.Hasil penelitian menunjukkan bahwa pemikiran Al-Maqrizi masih relevan dalam konteks ekonomi saat ini, terutama dalam memahami faktor-faktor yang mempengaruhi inflasi serta pentingnya kebijakan moneter yang stabil dan berkeadilan. Dengan demikian, kajian ini memberikan wawasan baru dalam mengevaluasi kebijakan moneter berdasarkan prinsip ekonomi Islam yang lebih berorientasi pada kesejahteraan masyarakat.